Improving Passenger Safety Through Automated Real-Time Validation of Driver - D. Gayathri (International Journal of Intelligent Systems and Applications in Engineering, 2024)
Our driver verification application aims to establish a secure and trustworthy platform for connecting customers, drivers, and service providers. Upon registration, drivers undergo a comprehensive verification process, including police verification, to ensure their legitimacy and adherence to safety standards. Customers can confidently request rides knowing that only verified drivers are part of the service. By incorporating essential security measures and privacy controls, the application strives to safeguard sensitive user data and ensure confidentiality throughout the platform. Our driver verification system serves as a reliable bridge between customers, drivers, and service providers, fostering a safe and efficient ride-hailing ecosystem. Through this application, we aim to promote transparency, accountability, and reliability while delivering an exceptional user experience for all participants involved.